HgTe quantum wells with inverted band structure: quantum Hall effect and the large-scale impurity potential - Gudina, S.V.; Arapov, Y.G.; Neverov, V.N.; Podgornykh, S.M.; Popov, M.R.; Deriushkina, E.V.; Shelushinina, N.G.; Yakunin, M.V.; Mikhailov, N.N.; Dvoretsky, S.A. (Физика низких температур, 2019)
We report on the longitudinal and Hall resistivities of a HgTe quantum well with inverted energy spectrum
(dQW = 20.3 nm) measured in the quantum Hall (QH) regime at magnetic fields up to 9 T and temperatures 2.9–50 K.
The temperature dependence of the QH plateau–plateau transition (PPT) widths and of variable range hopping
(VRH) conduction on the Hall plateaus are analyzed. The data are presented in a genuine scale form both for PPT
regions and for VRH regime. Decisive role of the long-range random potential (the potential of remote ionized impurities) in the localization–delocalization processes in the QH regime for the system under study is revealed. Експериментально досліджено поздовжній та холлівський
опори в квантовій ямі телуриду ртуті з інвертованим зонним
спектром (dQW = 20,3 нм), що виміряні в режимі квантового
ефекту Холла (КЕХ) в магнітних полях до 9 Тл та інтервалі
температур 2,9–50 К. Проаналізовано температурні залежності
ширини переходу між плато КЕХ та провідність зі змінною
довжиною стрибка в області плато КЕХ. Дані представлено в
універсальній скейлінговій формі як в області переходу між
плато, так і в режимі стрибкової провідності. Виявлено
вирішальну роль великомасштабного випадкового потенціалу
(віддалене легування через спейсер) в процесах локалізації–
делокализации носіїв заряду в режимі КЕХ в дослідженій
системі. Экспериментально исследованы продольное и холловское
сопротивления в квантовой яме теллурида ртути с инвертированным зонным спектром (dQW = 20,3 нм), измеренные в
режиме квантового эффекта Холла (КЭХ) в магнитных полях
до 9 Тл и интервале температур 2,9–50 К. Проанализированы
температурные зависимости ширины перехода между плато
КЭХ и проводимость с переменной длиной прыжка в области
плато КЭХ. Данные представлены в универсальной скейлинговой форме как в области перехода между плато, так и в
режиме прыжковой проводимости. Выявлена решающая
роль крупномасштабного случайного потенциала (удаленное
легирование через спейсер) в процессах локализации — делокализации носителей заряда в режиме КЭХ в исследованной системе.